Pengaruh Kebijakan Larangan Ekspor Batubara Terhadap Perusahaan Sektor Pertambangan Batubara Dan Mengidentifikasi Alternatif Strategi Berdasarkan Analisis SWOT Serta Metode AHP - BKL, Dhya Dhihqanda (Universitas Pahlawan Tuanku Tambusai, 2024)
Due to the critical condition of coal supply for domestic power plants, particularly PT PLN, the Indonesian government through the Ministry of Energy and Mineral Resources (ESDM) decided to temporarily halt coal exports for one month from January 1 to January 31, 2022. This decision negatively impacted coal companies whose majority of revenue comes from exports, potentially reducing their income and affecting investor interest, which could lead to a decline in the IDX Composite (IHSG) and impact Indonesia's economic growth. This study aims to identify the differences in stock prices of companies in the coal mining industry before and after this policy. The results show that between 12 months before the policy and 12 months after the policy, there is a significant difference in stock prices; however, post-policy stock prices are higher. This is because the policy was only in effect for one month and did not significantly impact companies focused on the domestic market. The study also identifies issues in the coal mining industry and formulates alternative strategies using SWOT analysis and the Analytical Hierarchy Process (AHP) method.